Model of Students’ Academic and Non-Academic Behaviours in Improving Learning Achievement and Discipline at Nurul ‘Ulum Modern Pesantren in Malang - Maunah, Binti (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
This research is aimed at describing academic and non-academic behaviours that influence students’ achievements and discipline. This research used qualitative method. The data was collected by using two main methods: participative observation and deep interview. There were four steps to analyze the data: data collection, data filter, data classification, and conclusion. Based on the result of the research and the discussion, it can be concluded that : 1). Generally, students have very good academic behaviours during learning process inside and outside the class, 2). Most of the students master English and Arabic skill in which it becomes the most prominent academic behaviour in modern pesantren, 3). Academic behaviours to improve opportunity and learning achievement were conducted by boarding system in which students don’t cook, don’t wash clothes, don’t bring cellphones, motorcycle, radio, TV, and other electronic tools, 4). Students perform very good non-academic behaviours in form of politeness to senior students and teachers, discipline and obey the rules of pesantren. It’s proved by no one is expelled from pesantren due to the violation of the rules of pesantren.